Al- Amṡāl al-‘Arabiyyah wa Dauruhā fī Ta’līm al-Lugah al-Arabiyyah li an-Nāṭiqīna bi Gairihā (Dirāsah Taṭbīqiyyah fi Ḍau’i Kitāb Jamharah al-Amṡāl li al-‘Askarī) - SalehDr. Saleh Muhammad Kabir; Ali Muhammad Usman (Jurnal Alsinatuna, 2022)
This study evaluated Arabic proverbs and their significance in teaching Arabic to non-Arabic speakers. This research employed a qualitative approach with a type of literature research. The primary data source was drawn from Jamharah al-Amṡāl, which was written by Abu Hilāl al-'Askarī's. The conclusions of this study reveal that Arabic proverbs can be utilized as a tool for the accomplishment of educational goals in society, changing the unfriendly to friendly attitude, and accomplishing particular aims in education. In the context of Learning Arabic, proverbs can be a means of realizing a general and specific purpose for the learner of Arabic due to several characteristics that exist in it: the simplicity of sentences, the precision of expression, the power of ideas, the beauty of tone, and the power of influence. In addition, learning content that comprises Arabic proverbs enables students to develop a literary taste when the content is prepared based on the correct scientific basis.